Deceived by stripes: conspicuous patterning on vital anterior body parts can redirect predatory strikes to expendable posterior organs. Issue 6 (June 2016) - Murali, Gopal; Kodandaramaiah, Ullasa
Abstract : Conspicuous coloration, which presumably makes prey more visible to predators, has intrigued researchers for long. Contrastingly coloured, conspicuous striped patterns are common among lizards and other animals, but their function is not well known. We propose and test a novel hypothesis, the 'redirection hypothesis', wherein longitudinal striped patterns, such as those found on the anterior body parts of most lacertilians, redirect attacks away from themselves during motion towards less vulnerable posterior parts, for example, the autotomous tail. In experiments employing human 'predators' attacking virtual prey on a touchscreen, we show that longitudinal striped patterns on the anterior half of prey decreased attacks to the anterior and increased attacks to the posterior. The position of stripes mattered—they worked best when they were at the anterior. By employing an adaptive psychophysical procedure, we show that prey with striped patterning are perceived to move slower, offering a mechanistic explanation for the redirective effect. In summary, our results suggest that the presence of stripes on the body (i.e. head and trunk) of lizards in combination with caudal autotomy can work as an effective anti-predator strategy during motion.